PAIN ETHOGRAM MAPPING: A MULTIDIMENSIONAL ANALYSIS OF BEHAVIORAL CHANGES IN CATTLE INFECTED WITH FOOT-AND-MOUTH DISEASE USING A VISUAL ANALOGUE SCALE - Nurdin, Muhammad Ardiansyah; Purba, Fika Yuliza; Bahmid, Nur ALif; Ismail, Irwan; Yusuf, Subaedy; Uskar, Muhammad Fath Maulana Binar; Thamrin, Muhammad Fathiyakan; Aulia, Nadisya; Ngopo, Frinth Azarya Kuriakos; Oktavia, Christin; et al. (Buletin Veteriner Udayana, 2026)
Foot-and-mouth disease (FMD) is a highly contagious viral disease that causes severe pain and compromises cattle welfare. Objective pain assessment is challenging but essential for effective therapeutic management. This study aimed to comprehensively characterize the pain profile in FMD-infected cattle by validating the use of the visual analog scale (VAS) through a multidimensional analysis of pain behavioral manifestations. To ensure robustness, the validation process included inter-rater reliability assessments and a comparison with established pain indicators, addressing concerns about the VAS's reproducibility. This qualitative descriptive study was conducted on 15 FMD-infected cattle in Makassar City and Gowa Regency. Pain intensity was evaluated using the VAS based on direct observation of a series of behavioral parameters. The results indicated heterogeneity in pain intensity across parameters. Locomotor deficits, such as lameness and slowness, as well as agitation (restlessness), consistently correlated with moderate pain levels. Conversely, interactive responses, such as aggression and most postural changes, were identified in the mild pain category. It was concluded that the VAS is a valid and reliable instrument for multidimensional pain assessment in FMD-infected cattle, with mobility and agitation being the most significant markers for the early detection of moderate pain.